Comparative Genome Analysis of Staphylococcus lugdunensis Shows Clonal Complex-Dependent Diversity of the Putative Virulence Factor, ess/Type VII Locus - Lebeurre, Jérémie; Dahyot, Sandrine; Diene, Seydina; Paulay, Amandine; Aubourg, Marion; Argemi, Xavier; Giard, Jean-Christophe; Tournier, Isabelle; François, Patrice; Pestel-Caron, Martine (Frontiers in Microbiology, 2019)
Staphylococcus lugdunensis is a commensal bacterium of human skin that has emerged as a virulent Coagulase-Negative Staphylococcus in both community-acquired and healthcare associated infections. Genotyping methods have shown a clonal population structure of this pathogen but failed to identify hypervirulent lineages. Here, complete genomes of 3 pathogenic and 3 carriage S. lugdunensis strains were obtained by Single-Molecule sequencing (PacBio) and compared to 15 complete genomes available in GenBank database. The aim was to identify (i) genetic determinants specific to pathogenic or carriage strains or specific to clonal complexes (CCs) defined by MultiLocus Sequence Typing, and (ii) antibiotic resistance genes and new putative virulence factors encoded or not by mobile genetic elements (MGE). Comparative genomic analysis did not show a strict correlation between gene content and the ability of the 6 strains to cause infections in humans and in a Galleria mellonella infection model. However, this study identified new MGEs (5 prophages, 2 genomic islands and one plasmid) and genetic variations of some putative virulence-associated loci, especially in CC3 strains. For a clonal population, high variability and 8 CC-dependent genetic organizations were observed for the ess locus, which encodes a putative type VII secretion system (T7SS) homologous to that of S. aureus. Further phenotypic and functional studies are needed to characterize this particular CC3 and to evaluate the role of T7SS in the virulence of S. lugdunensis.